Structural equation modelling of construction waste root causes and waste generation rate in Malaysian construction industry - Kaliannan, Suaathi (2021)
Construction is one of the vital sectors in the economic growth, especially for a developing country like Malaysia. The rapid development of this industry is causing a huge amount of construction waste generated on site. Besides, illegal dumping of construction waste is quite a typical scenario in Malaysia which has been frequently published in the local newspapers and previous scholarly literature. Construction waste results from various causes which are necessary to be identified for reducing the waste generated in the construction project. Therefore, to overcome these problems, the root cause of the construction waste generation needs to be determined. The research aims to develop a structural relationship model between the root cause and waste generation rate for Malaysian construction industry. The quantitative approach, through a structured questionnaire survey is used to verify the root cause and determine the construction waste generation rate. A total of 321 questionnaire forms were received and analysed using factor analysis technique in SPSS software. The factor analysis resulted in 5 groups of root causes namely design and documentation, human resource, materials and equipment, project management and external. Furthermore, 12 types of material waste generation level were gathered through the questionnaire and the findings revealed that, timber and concrete waste are highly generated on site. Next, the relationship between the root causes of the construction waste and material waste generation rate was established using the advanced multivariate approach of the Partial Least Square-Structural Equation Modelling (PLS-SEM). It results that the performance of the model has a moderate explaining power ability with the value of R2 = 0.319, which is substantial. The model identifies that all 5 groups are significant with t-value ≥ 2.58 from bootstrapping process. The model indicates that design and documentation group has the highest impact on the material waste generation rate. In addition, the model was validated and verified by construction experts where 94% of them agreed with the findings. Therefore, the model has the potential to aid the construction practitioners to reduce the construction waste generation in construction projects by focusing on the critical root causes established.